Restructuring cowpea for higher yield - Singh, B.B.; Sharma, B. (1996)
The cowpea breeding programmes are reviewed and achievements at two major centres of cowpea research, i.e. IITA (Nigeria) and IARI (India), are summarized. Earlyand extra early genotypes are always photoperiod-insensitive, medium maturity varieties could be sensitive or neutral today length, while late varieties are always highly sensitive to photoperiod. It has been demonstrated that with the availability of short or medium duration varieties having erect plant type and resistant to major diseases, stable yields in the range of 25–30 q/ha can be obtained under appropriate crop management. Even early maturing varieties have yielded up to 29.88 q/ha in isolated trials. Breeding for insect resistance continues to be an uncertain area, while varieties resistant to major viral, bacterial and fungal diseases have been developed. Photoperiod-neutral varieties (which are also early maturing) possess wider adaptability. It has been demonstrated that high grain yield can be combined with high harvest index in the early and extra-early varieties, maturing in 60–65 days. The future varieties of cowpea should combine high yields with upright growth habit, bushy plant type, determinate flowering, early-medium maturity, and long peduncles keeping the pods above the plant canopy. Attempts are in progress to evolve varieties which can tolerate shady conditions of mixed cropping with tall cereals like maize, sorghum and pearl millet, as well as varieties for dual (grain-fodder, grain-vegetable) purpose.